PENGARUH MODEL KONTEKSTUAL TERHADAP HASIL BELAJAR PPKN SISWA KELAS XI IPS - Herwinda Nurlaily; Aminuyati Aminuyati; Bambang Budi Utomo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research was implemented due to the low number of students that showed their interest in listening to the material explaining by the teacher. The goal of this research was to make the teaching and learning process be more useful for the students. Therefore, the researcher was doing an experimental study by using contextual model (contextual teaching and learning) which was aimed to know the effect of the use of contextual model (contextual teaching and learning) to the students’ learning result of class XI IPS 4 at SMAN 4 Pontianak. The research method used was experimental study method in pre-experimental design one-group pretest-postest design form. In pre-test, the average of students’ score was 69.68, meanwhile in post-test the average of students’ score was 79.84. As the result of the research finding in paired test sample, t-test showed that the number of significancy (2-tailed) was 0.000. This finding proved that the significancy number (2-tailed) <0.05 which showed the effect of contextual model (contextual teaching and learning) to the students’ learning result in PPKN subject of class XI IPS 4 at SMAN 4 Pontianak. The result of the calculation of the effect size was a strong effect since the number of the effect size was 1.562>1.00. Therefore, it can be concluded that the use of contextual model (contextual teaching and learning) was effectively affect the students’ learning result especially for “Faktor Pendorong dan Penghambat Persatuan dan Kesatuan Bangsa” material. Keywords: Contextual Model, Effect, The result of teaching and learning process of PPKN subject